Global justice and the politics of information the struggle over knowledge - Croeser, Sky (Rethinking globalizations, 2015)
Drawing on extensive interviews and fieldwork, this book illustrates the importance of contributions from local movements around the world to the struggle for global justice. Including detailed case studies on opposition to genetically-modified crops in the south of India, and the digital liberties movement, this book is vital reading for anyone trying to understand the changing relationship between science, technology, and progressive movements around the world